1999
DOI: 10.1074/jbc.274.32.22627
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinases-3, -7, and -12, but Not -9, Reduce High Density Lipoprotein-induced Cholesterol Efflux from Human Macrophage Foam Cells by Truncation of the Carboxyl Terminus of Apolipoprotein A-I

Abstract: Matrix metalloproteinases (MMPs) have been suggested to function in remodeling of the arterial wall, but no information is available on their possible role in early atherogenesis, when cholesterol accumulates in the cells of the arterial intima, forming foam cells. Here, we incubated the major component responsible for efflux of cholesterol from foam cells, high density lipoprotein 3 (HDL 3 ), with MMP-1, -3, -7, -9, or -12 at 37°C before adding it to cholesterol-loaded human monocyte-derived macrophages. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 60 publications
5
47
0
5
Order By: Relevance
“…Stromelysin degrades almost all of the apoA-I without causing any apparent change in apoA-II, whereas the 92 kDa gelatinase appears to degrade apoA-II only (28). The present results with rHDL containing either apoA-I or apoA-II as a single protein component show that chymase clearly distinguishes between apoA-I, which is degraded, and apoA-II, which is completely resistant to proteolytic digestion by the enzyme.…”
Section: Discussionsupporting
confidence: 50%
“…Stromelysin degrades almost all of the apoA-I without causing any apparent change in apoA-II, whereas the 92 kDa gelatinase appears to degrade apoA-II only (28). The present results with rHDL containing either apoA-I or apoA-II as a single protein component show that chymase clearly distinguishes between apoA-I, which is degraded, and apoA-II, which is completely resistant to proteolytic digestion by the enzyme.…”
Section: Discussionsupporting
confidence: 50%
“…Previous in vitro studies demonstrated that several proteases, including matrix metalloproteases (14), plasmin and kallikrein (15), and two mast cell proteases, chymase and tryptase (8), can degrade apoA-I present in preb-HDL particles, thereby impairing cellular cholesterol efflux. In this report, we show that TTR has a similar effect: not only does TTR cleave apoA-I in the C terminus after the same residue as chymase (phenylalanine 225) (5), but TTR also is more effective at cleaving apoA-I present in lipid-poor preb-HDL particles, resulting in an impairment in the ability of rHDL to promote cholesterol efflux from macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several proteases found in the arterial intima, such as elastase (13), metalloproteases (14), plasmin and plasma kallikrein (15), and the mast cell proteases chymase and tryptase (8), degrade apoA-I in preb-HDL particles in vitro. A crucial prerequisite for the action of HDL particles as efficient acceptors of cellular cholesterol is their integrity; in agreement with this concept, apoA-I cleavage by the above proteases has been widely demonstrated to impair the high-affinity component of cellular cholesterol efflux.…”
Section: Supplementary Abstract High Density Lipoprotein and Reverse Cmentioning
confidence: 99%
“…The mast cell proteases chymase (20) and tryptase (21) and some metalloproteinases (22) as well as plasmin and kallikrein (23) specifically deplete the small subpopulation of pre-␤-migrating HDL particles and so impair the efflux of cholesterol from human macrophage foam cells promoted by HDL 3 . Because cholesterol efflux to HDL 3 can be mediated by ABCA1-dependent and -independent mechanisms, we were interested to find out which of these two types of efflux is affected by proteolytic enzymes capable of depleting pre-␤-migrating HDL particles.…”
mentioning
confidence: 99%